AI-Driven Verification for Compute Express Link (CXL): Challenges, Innovations, and Future - Deepak Kumar Lnu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution and challenges of Compute Express Link (CXL) verification methodologies in modern computing environments. The article examines the critical aspects of cache coherency testing, compliance validation, and debugging strategies while highlighting the transformative role of artificial intelligence in enhancing verification processes. The article demonstrates how advanced methodologies address the complexities of heterogeneous computing systems by analyzing various verification approaches, including AI-driven compliance automation, predictive debugging, and adaptive testbenches. The article encompasses memory device verification performance, system-level integration, and future directions in CXL verification, providing insights into emerging technologies and methodologies for ensuring robust system validation.